PERAN ORANG TUA DALAM MENDAMPINGI KEGIATAN BERMAIN GADGET PADA ANAK USIA DINI DUSUN LOROKAN RT 012 RW 004 DESA BOTO KECAMATAN LUMBANG KABUPATEN PROBOLINGGO - Maslahah, Siti; Dirgayunita, Aries (LPPM IAD Probolinggo, 2024)
The role of parents in accompanying gadget playing activities in early childhood is very important because parents are the closest family to children, parents must play an active role in efforts to protect children. The aim of this research is to determine the role of parents in accompanying children's gadget playing activities. aged 5-6 years. This research used qualitative methods. This research was conducted in Lorokan Hamlet RT 12 RW 004 Boto Village, Lumbang District, Probolinggo Regency. The research time was September to November. The research subjects were parents who had children aged 5-6 years. and the number of informants was 6 heads of families who had children aged 5-6 years. Data collection techniques used observation, interviews and documentation. The results of the research were that parents introduced modern forms of technology to young children such as cellphones, laptops, etc. Parents set limits time when using gadgets in early childhood by limiting the time of use, so when can children play and stop playing with gadgets. Parents give moral values ​​to young children when using gadgets through the applications on the gadget so that it is easier to set a role model for children through interesting stories on gadgets. Parents provide supervision in using gadgets for children by supervising children when playing with gadgets. Keywords: Role of Parents, Gadgets, Early Childhood